2015
DOI: 10.1038/ni.3314
|View full text |Cite
|
Sign up to set email alerts
|

The cytotoxic T cell proteome and its shaping by the kinase mTOR

Abstract: High-resolution mass spectrometry maps the cytotoxic T lymphocyte (CTL) proteome and the impact of mammalian target of rapamycin complex 1 (mTORC1) on CTLs. The CTL proteome was dominated by metabolic regulators and granzymes and mTORC1 selectively repressed and promoted expression of subset of CTL proteins (~10%). These included key CTL effector molecules, signaling proteins and a subset of metabolic enzymes. Proteomic data highlighted the potential for mTORC1 negative control of phosphatidylinositol (3,4,5)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
226
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(243 citation statements)
references
References 49 publications
13
226
4
Order By: Relevance
“…In contrast, CD25 expression, which was already present on the surface of T lymphoblasts, was only increased when T cells were activated on the aCD3+aCD28+ICAM-1-coated stiff 100 kPa gels (Figure 4C and D), whereas its gene expression was increased from 0.5 kPa (Figure 2C). These last results may be explained by the differences between transcriptomic and proteomic analyses that have already been reported (Hukelmann et al, 2016). They might also reflect a difference in sensitivity for the different measurements performed.
10.7554/eLife.23190.015Figure 4.Cytokine production is sensitive to a wide range of stiffness.Production of ( A ) IFNγ (n Donors : 13) and ( B ) TNFα (n Donors : 10) on PA-gels of varying stiffness.
…”
Section: Resultsmentioning
confidence: 88%
“…In contrast, CD25 expression, which was already present on the surface of T lymphoblasts, was only increased when T cells were activated on the aCD3+aCD28+ICAM-1-coated stiff 100 kPa gels (Figure 4C and D), whereas its gene expression was increased from 0.5 kPa (Figure 2C). These last results may be explained by the differences between transcriptomic and proteomic analyses that have already been reported (Hukelmann et al, 2016). They might also reflect a difference in sensitivity for the different measurements performed.
10.7554/eLife.23190.015Figure 4.Cytokine production is sensitive to a wide range of stiffness.Production of ( A ) IFNγ (n Donors : 13) and ( B ) TNFα (n Donors : 10) on PA-gels of varying stiffness.
…”
Section: Resultsmentioning
confidence: 88%
“…It is important to keep in mind that PI3Kδ regulates other pathways in addition mTOR, and conversely, that mTOR is also regulated byPI3K-independent pathways8. Moreover, mTOR regulates the expression of PTEN such that treatment of T cells with rapamycin can actually increase PI3K signalling in T cells84, potentially exacerbating aspects of hyperactive PI3Kδ signalling in APDS.…”
Section: Treatment Options For Patients With Apdsmentioning
confidence: 99%
“…Proteomic analysis of Raptor-deficient T cells shows that expression of key transcription factors in metabolic reprogramming (MYC, YY1, GABPA, SREBF1) and components of the translational machinery are dependent upon mTORC1 (Tan et al, 2017), highlighting the central role of mTORC1 in anabolic T cell growth. Moreover, in cytotoxic CD8 + T cells, proteomic analyses have shown that rapamycin treatment to inhibit mTORC1 causes a reduction in cell size and protein content associated with changes in abundance (up as well as down) of approximately 10% of the proteome, including reductions in glucose transporters, and enzymes in the glycolysis and cholesterol synthesis metabolic pathways, as well as of the PtdIns(3,4,5)P3 phosphatase PTEN, and key effector proteins such as IFN-γ, perforin granzyme, and TNFα (Hukelmann et al, 2016). These changes are generally related to rapamycin-induced reductions in transcription of the encoding genes, although outside of these pathways clear mTORC1-dependent differences in protein levels in the absence of effects on transcription are measurable.…”
Section: Metabolic Sensing By Mtor and Competition For Nutrients Withmentioning
confidence: 99%